Jogos de estratégia de guerra em tempo real multijogador e seu desenvolvimento no Motor Unreal Engine 4 - Peixoto, Cesar da Silva (2019)
The main objective of this research is develop a study on real-time war strategy games, contemplating the fundamentals elements in a game design, and its developing process, using as a base the standard resources of Unreal Engine 4. What justifies this investigation is the lack of debate about the proposed theme, specialy in Brazil it has a lack of study in this área, even more when compare with the other academic areas. What motivates this research would be a possibility to find out new alternatives tha could contribute with the evolution of the independente game development industry in Brazil, encouraging a development of a game genere nowadays underexplored for the biggest studios, and it can bem explored using the comercial tools offering on the market.The presente investigation is seeking answer the question: How the multiplayer online real-time strategy games can be developed using Unreal Engine 4? Considering a hypothesis that Unreal Engine 4, through the native technology itself has, it viable to develop multiplayer online real-time stategy games on the independente games industry scenario. We opted using the methodology of scientific research of a qualitative nature, kind of desciptive, with bibliographical / documental data origin, with na execution in a filed under epistemological prism of Design Science Research, as it has a theoretical and empirics aspect, to accomplish the general objective. The review of previous studies on the theme was between 2008 and 2018, including books, scientific articles, thesis and dissertations, considering possible online searches avalible: a) Banco de Teses e Dissertações da PUC-SP (Pontifícia Universidade Católica de São Paulo), b) Banco de Teses e Dissertações da Capes, c) SBGames – Sociedade Brasileira de Games, d) The International Journal of Computer Game Research, e) Google Scholar. Also were considered for previous study reviews, available articles at Scientific Electronic Library Online – SciELO, from the scientific magazines classified as A1 level by Qualis-Capes in the interdisciplinar and computer Science. The collection data will be done by surveys, interview and observation. The theorical references that suport this investigation are games concepts (HUIZINGA, 2017; CAILLOIS, 2017), strategy digital games (NOVAK, 2010) and game design for digital games (MCGONIGAL, 2012; SCHELL, 2011). The results achieved have got the general and established specific objectives, however, the hypothesis showed untrue in this study, due to standard navigation system, offered by Unreal Engine 4, that was unsuitable for the develop of real-time strategy games